Longitudinal investigation of mineral composition in human milk and its correlation with infant anthropometric outcomes among Tibetan mother-infant dyads during the first 6 months postpartum - Xiaomei Zhang; Yaling Wang; Junying Zhao; Weicang Qiao; Yanpin Liu; Lijun Chen (Food Science and Human Wellness)
Nutrients in human milk, including minerals, relate growth and development of breast-fed infants. Tibetan mother-infant dyads possess unique characteristics on early nutrition due to their featured long-lasting life-style. This study longitudinally investigated the relationship between the mineral composition in human milk and the Z-scores of infants among Tibetan mother-infant dyads during their first 6 months postpartum through a prospective cohort study. The results show that the minerals of Na, Mg, K, Ca, Cu, Zn, and Se were of higher levels in colostrum than other lactation stages. Several minerals were below the recommended values for infants according to Chinese dietary guidelines. Besides, a large proportion of infant Z-scores were below −2 as lactation period continued. Multivariate statistical analysis revealed that classifications and correlations in varying degrees were observed between minerals in human milk and infant Z-scores. These findings will be advantageous for research upon Chinese early nutrition and progress of tailor-made infant formula.